Genocide and Reconciliation in Rwanda : The Experiences of Children - McKlveen, Sarah; Rice, Louisa C. (My University, 2017)
By the end of April 1994, a genocide against Tutsis and moderate Hutus had already taken hold of the small nation-state of Rwanda, instigated by extremist Hutus. In the wake of the ethnic cleansing came a death toll of around 800,000 Rwandans, with nearly 300,000 children exterminated and another 95,000 orphaned. This project argues that children were targeted as explicitly and aggressively as their adult counterparts, suggesting that they were not viewed as “protected” persons regardless of their innocence. Through an analysis of children’s testimonies, we can more fully understand their experiences as well as how these young people are coping in post-Genocide Rwanda.
Color poster with text, charts, images and graphs.
Keywords: Children; Genocide; Rwanda; Posters